Micromachining NiTi tubes for use in medical devices by using a femtosecond laser. (March 2015) - Hung, Chia-Hung; Chang, Fuh-Yu; Chang, Tien-Li; Chang, Yu-Ting; Huang, Kai-Wen; Liang, Po-Chin
Abstract: Recent growth in medical device technology has been substantially driven by developments in laser micromachining, which is a powerful fabrication technique in which nickel–titanium (Nitinol, NiTi) alloy materials that exhibit superelastic and shape memory properties are formed (e.g., self-expanding stents). In this study a NiTi tube curve surface process is proposed, involving a femtosecond laser process and a galvano-mirror scanner. The diameter of the NiTi tube was 5.116 mm, its thickness was 0.234 mm, and its length was 100 mm. The results indicated that during the machine process the ablation mechanism of the NiTi tubes was changed by altering the machining path. The path alteration enhanced the laser ablation rate from 12.3 to 26.7 μm/J. Thus the path alteration contributed to a wide kerf line, enabling the assisted air to efficiently remove the debris deposited at the bottom of the kerf during the laser ablation process. The results indicated that the NiTi tube curve process enhanced the laser ablation rate by two times and reduced the amount of energy accumulated within the materials by 50% or more. By altering the machining path using the scanning system, this process can decrease the production of heat affected zones (the accumulation of thermal energy) in medical device applications. Highlights: A NiTi tube curve surface process is proposed. The process uses femtosecond laser irradiation with a galvano-mirror scanner. Process can decrease the production of heat affected zones in medical device applications.